2022
DOI: 10.1002/cbdv.202100843
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Thioinosine and Butenolides from a Terrestrial Actinomycetes sp. GSCW‐51 and Their in Silico Studies for Potential against SARS‐CoV‐2

Abstract: In our continuous screening for bioactive microbial natural products, the culture extracts of a terrestrial Actinomycetes sp. GSCW‐51 yielded two new metabolites, i. e., 5‐hydroxymethyl‐3‐(1‐hydroxy‐6‐methyl‐7‐oxooctyl)dihydrofuran‐2(3H)‐one (1), 5‐hydroxymethyl‐3‐(1,7‐dihydroxy‐6‐methyloctyl)dihydrofuran‐2(3H)‐one (2), and two known compounds; 5′‐methylthioinosine (3), and 5′‐methylthioinosine sulfoxide (4), which are isolated first time from any natural source, along with four known compounds (5–8). The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Additionally, research was done to evaluate the pharmacokinetics, drug-likeness, and quantitative structure-activity relationship (QSAR) of these compounds (63). The findings revealed that C-5 had the best pharmacokinetic and drug-like characteristics, making it a good candidate for further development and optimization as a medication to treat COVID-19 (64).…”
Section: Computational Methods For Sars-cov-2 Protease Inhibitor Iden...mentioning
confidence: 99%
“…Additionally, research was done to evaluate the pharmacokinetics, drug-likeness, and quantitative structure-activity relationship (QSAR) of these compounds (63). The findings revealed that C-5 had the best pharmacokinetic and drug-like characteristics, making it a good candidate for further development and optimization as a medication to treat COVID-19 (64).…”
Section: Computational Methods For Sars-cov-2 Protease Inhibitor Iden...mentioning
confidence: 99%